The studies on different scaling factor for microstrip antenna design - Abd. Aziz, Mohamad Zoinol Abidin; A. Rahim, Mohamad Kamal; Asrokin, A. (2005)
This paper had studied the effect of different scaling factor (tau) to microstrip log periodic antenna. Two value of scaling factor (tau) 1.02 and 1.05 had been studied. The bandwidth of the antenna has increase from 10.65% to 23.92% as bigger scaling factor were used. Five element antennas were applied in both designs. The simulation for the five elements was done using circuit simulator. The etching technique was applied in the fabrication process by using the FR4 microstrip board with dielectric constant 4.7 and loss tangent is 0.019. The properties of antenna such as bandwidth, gain, cross-polar isolation and half power beamwidth have been investigated and compared between simulation and measurements.